2015
DOI: 10.3986/ags.753
|View full text |Cite
|
Sign up to set email alerts
|

Structural dynamics of tertiary activities in industrial parks in Bucharest, Romania

Abstract: The study is an analysis of tertiarization in Bucharest, a process that tends to become dominant inside an economic system that has faced the hardships of transition and reorganization. The study deals with tertiarization inside the industrial parks in the capital city, in close connection with deindustrialization and industrial delocalization. The study highlights the forms tertiarization has taken inside those areas, former industrial platforms of the utmost importance for the industry of the Communist era. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Big commercial investments have been made on the site of former industrial units that had been demolished (Cercleux, Peptenatu and Merciu 2015), or on some former production spaces, former farm lands located on the outskirts of large cities, or in peri-urban zones (using existing road access), in some residential areas short of services facilities, or in the proximity of some student camps.…”
Section: Discussionmentioning
confidence: 99%
“…Big commercial investments have been made on the site of former industrial units that had been demolished (Cercleux, Peptenatu and Merciu 2015), or on some former production spaces, former farm lands located on the outskirts of large cities, or in peri-urban zones (using existing road access), in some residential areas short of services facilities, or in the proximity of some student camps.…”
Section: Discussionmentioning
confidence: 99%
“…Paper by Romanian authors deals with tertiarization inside the industrial parks in the capital city, in close connection with deindustrialization and industrial delocalization (Cercleux, Peptenatu, Merciu, 2015). An example of research in Portugal is also cited, where it was confirmed that the increase and diversification of foreign direct investment coincided with the tertiarization of the economy, being closer to the productive specialization pattern of the country, while continuing to focus mainly on manufacturing (Melo, Ferreira-Lopes, Monteiro, 2015).…”
Section: Overview Of Previous Researchmentioning
confidence: 97%
“…Then, the performance of various economic sectors was very different. Industry, developed as the key economic sector in socialist countries, was especially affected by the transition (Cercleux et al, 2015). Thus, many thriving industrial plants from the socialist period are abandoned today (Figure 3).…”
Section: Economic Criterionmentioning
confidence: 99%